Recommender system for drivers of electric vehicles - Ferreira, João C. (2011)
Being the next big step in automobile industry, electric vehicles continue to have limited autonomy which associated with the long charging times, limited charging stations and undeveloped smart grid infrastructure demands for a hard planning of the daily use of the vehicle. This paper presents an information system that will help the driver in the daily use of his electric vehicle, minimizing the problem of range anxiety thru the continuous control of the vehicle range and presenting in time relevant information about the charging stations within reach. Given the success of recommendation systems on automatically delivering the relevant information in numerous areas of usage, it can be applied in this scenario as well as with the objective of maximizing the relevance of the information presented to the driver, which should be the strictly needed for him to make his decisions filtering out the unnecessary one.